Why public administration is needed now more than ever: Advancing the scholarship of teaching and learning in public administration: First Public Lecture sponsored by Teaching Public Administration (delivered at the Public Administration Conference, University of Northumbria 12 September 2018). Issue 2 (July 2019) - Dunning, Pamela T
First Public Lecture sponsored by Teaching Public Administration (delivered at the Public Administration Conference, University of Northumbria 12 September 2018). The author provided views on why public administration is needed now more than ever, outlining how current events necessitate the need for research to inform our teaching and learning. She also discussed some of the barriers to this task, and her views of the future.